(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Drugs inevitably produce unwanted effects. Legally, there exist various provisions and acts to regulate the manufacturing, prescription, administration and dispensing of drugs. Hence, consistent care is needed at every stage, from drug manufacture to administration, to avoid legal consequences. The present article is an overview of these regulations and usage of drugs.